Radiological semiology in emergency brain pathology: Semiología Radiológica en Patología Cerebral de Emergencia - Román Meza, Alexander Humberto (2019)
Radiology is a great tool in the diagnosis of encephalic pathologies, especially in situations of neurological urgency and emergency, to rule out the presence of a specific pathology, and to definite the location and size of the lesion, or clarify an initial uncertain diagnosis. In this way, the knowledge of its main signs, findings and characteristics is important to perform an adequate examination, because it facilitates the description of the images obtained with greater speed and precision allowing an optimal and immediate labor of the treating doctor in favor of the patient. Therefore, this article presents a brief review of the representative radiological semiology obtained in the medical literature, where the references were bibliographies and researches, which is convenient to localize the signs that could exist as soon as the examination was obtained, for the future therapeutic of the patient, such as the possibility of extension in the radiology exam or suggestion by the medical technologist of radiology in coordination with the requesting physician to guarantee the patient's care effective.